Relationship between knowledge level model soapie (nursing process) and quality of nursing records in the ICU of the Regional Teaching Hospital Maternal And Child “El Carmen” Huancayo 2013 - Suasnabar Cueva, Edith (2020)
OBJECTIVE: The research paper entitled “Relationship between the level of knowledge of the model soapie (nursing process) and quality of nursing records in the ICU of the Regional Teaching Hospital Mother and Child” El Carmen - Huancayo 2013 “, formulated the object; To determine the relationship between the level of knowledge soapie model and the quality of the annotations of Nursing. MATERIALS AND METHODS: Retrospective descriptive correlational study. The study population was Nine nurses working in the ICU of the hospital under study;) Instrument; questionnaire and a checklist, the survey technique was used; validation and reliability of the instrument was performed using Cronbach Alpha test, the statistical analysis was performed using SPSS software application Version 21 results. RESULTS: Where he made use of descriptive statistics and inferential statistics for the corresponding hypothesis test by Student t for α = 0.05 and 95% confidence level it is shown that there is a positive correlation between the scores the level of knowledge and soapie model scores the quality of nursing notes. There is a significant direct relationship between the level of knowledge soapie model and the quality of the entries in Nursing Intensive Care Unit of the Regional Teaching Hospital Maternal and Child El Carmen Huancayo.